2008
DOI: 10.1590/s1806-37132008000400010
|View full text |Cite
|
Sign up to set email alerts
|

Tratamento da actinomicose pulmonar com levofloxacina

Abstract: Actinomycosis is a chronic suppurative bacterial infection characterized by multiple abscesses, fistulous pathways, and fibrosis involving the face, neck, chest, and abdomen. It is caused by an anaerobic Gram-positive saprophytic bacterium (Actinomyces). Primary actinomycosis of the lung is a rare disease that probably results from aspiration of oropharyngeal secretions. It can present as a chronic respiratory disease. The treatment of choice is antibiotic therapy with penicillin. The authors report the case o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The 3 most common symptoms of pelvic actinomycosis are abdominal pain, weight loss, and abnormal vaginal discharge. It is reported that 60% of patients also have fever, and the clinical manifestations are less severe than the lesion [ 11 , 12 ]. In severe cases, a sinus tract or fistula is formed, and solid masses with fixed and unclear boundaries are formed, and even “frozen pelvis” can occur.…”
Section: Discussionmentioning
confidence: 99%
“…The 3 most common symptoms of pelvic actinomycosis are abdominal pain, weight loss, and abnormal vaginal discharge. It is reported that 60% of patients also have fever, and the clinical manifestations are less severe than the lesion [ 11 , 12 ]. In severe cases, a sinus tract or fistula is formed, and solid masses with fixed and unclear boundaries are formed, and even “frozen pelvis” can occur.…”
Section: Discussionmentioning
confidence: 99%
“…Although Actinomyces reside in the oropharynx and gastrointestinal tract, and are normally avirulent in healthy individuals (5,6), Actinomyces -associated diseases can occur in individuals with particular host characteristics [e.g., aspiration, alcohol abuse, periodontal disease, chronic obstructive pulmonary disease (COPD), and diabetes mellitus] (7). Pulmonary actinomycosis is relatively rare (8), and is thought to result from the aspiration of Actinomyces into the lungs (9). Although chest imaging of pulmonary actinomycosis most commonly reveals fibrotic infiltrates that are confined to a single lobe with small cavitary lesions (10), non-specific findings are commonly observed in clinical practice (11-13).…”
Section: Discussionmentioning
confidence: 99%